THE ROLE OF SOCIAL ENTREPRENEURSHIP IN IMPROVING THE QUALITY OF LIFE OF THE CUSTOMER Field research at the Iraqi Ministry of Labor and Social Affairs - سعيد, سناء عبد الرحيم; عبد الزهرة, زينة رائد (Journal of Economics and Administrative Sciences, 2019)
Abstract:       This research emerged due to the needs of Iraqi social sector for diagnosing the problems ,finding the appropriate solutions,and exploiting the social opportunities to solve these problems .The research problem focused on raising the following question: "Were Iraqi Managers in the Ministry of Labor and Social Affairs able to use their qualifications as social entrepreneurs in the ministry to improve the quality of life of the disadvantaged groups?", In light of that, the importance and objectives of the study were determined, and this research derives its importance from trying to address social problems by measuring the degree of meeting the subjective and objective needs of the customer to improve living, The research aims to achieve a number of objectives including access, Including the access to results that underpin the frame of research variables (social entrepreneurship, the quality of life of the customer) and formulating the hypotheses of correlation and influences of research  variables. It is conducted  a field study on ten social programs implemented  in a number  of departments of the Iraqi Ministry of Labor and Social Affairs in Baghdad governorate (Security of private sector employees, Social welfare, registration and employment of the unemployed, a national program for the control of occupational diseases, training of the unemployed, economic and social empowerment of women, support for small income-generating projects-loans, social housing for the elderly, full-time appointment, and Exemptions for people with disabilities and special needs), The community of research consists of the managers of these ten programs in the ministry. It chooses a random sample consists of (200) managers of these programs. This research is based on two approaches– descriptive approach in the theoretical side and the field study in the practical side for analyzing the questionnaire. the reality of the variables of the research were addressed and analyzed for the selected sample. Then, the hypotheses of correlation were tested by using correlation coefficient (Pearson). The hypotheses of influence were tested by using the approach of Structural Equation Modeling (SEM). A number of software such as Excel. V.2010, SPSS.V.24, and AMOS.V.24. were used for quantitatively analyzing data and finding the results. The results showed the validity of correlation and the influences hypotheses for the variables. The main recommendations focused on recruitment of individuals with experience and qualifications in the social entrepreneurship field consistent with Iraqi environment in order to improve the quality of life for customers (beneficiaries from the services of ministry).